The Impact on Staff of Working with Personality Disordered Offenders: A Systematic Review. - Mark C Freestone; Kim Wilson; Rose Jones; Chris Mikton; Sophia Milsom; Ketan Sonigra; Celia Taylor; Colin Campbell (PLoS ONE)
Background Personality disordered offenders (PDOs) are generally considered difficult to manage and to have a negative impact on staff working with them. Aims This study aimed to provide an overview of studies examining the impact on staff of working with PDOs, identify impact areas associated with working with PDOs, identify gaps in existing research,and direct future research efforts. Methods The authors conducted a systematic review of the English-language literature from 1964-2014 across 20 databases in the medical and social sciences. Results 27 papers were included in the review. Studies identified negative impacts upon staff including: negative attitudes, burnout, stress, negative counter-transferential experiences; two studies found positive impacts of job excitement and satisfaction, and the evidence related to perceived risk of violence from PDOs was equivocal. Studies demonstrated considerable heterogeneity and meta-analysis was not possible. The overall level of identified evidence was low: 23 studies (85%) were descriptive only, and only one adequately powered cohort study was found. Conclusions The review identified a significant amount of descriptive literature, but only one cohort study and no trials or previous systematic reviews of literatures. Clinicians and managers working with PDOs should be aware of the potential impacts identified, but there is an urgent need for further research focusing on the robust evaluation of interventions to minimise harm to staff working with offenders who suffer from personality disorder.